2015
DOI: 10.1002/jobm.201400774
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating genetic diversity and constructing core collections of Chinese Lentinula edodes cultivars using ISSR and SRAP markers

Abstract: Genetic diversity among 89 Chinese Lentinula edodes cultivars was analyzed by inter-simple sequence repeat (ISSR) and sequence-related amplified polymorphism (SRAP) markers. A 123 out of 126 ISSR loci (97.62%) and 108 out of 129 SRAP loci (83.73%) were polymorphic between two or more strains. A dendrogram constructed by cluster analysis based on the ISSR and SRAP markers separated the L. edodes strains into two major groups, of which group B was further divided into five subgroups. Clustering results also show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 37 publications
(61 reference statements)
1
18
0
1
Order By: Relevance
“…This is consistent with previous clustering analyses which revealed that ZP85 was distinctly different from other cultivars79. This strain was recently developed from a Chinese wild strain by the Guangdong Institute of Microbiology, and this may be the reason why it was not grouped with the other cultivars.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is consistent with previous clustering analyses which revealed that ZP85 was distinctly different from other cultivars79. This strain was recently developed from a Chinese wild strain by the Guangdong Institute of Microbiology, and this may be the reason why it was not grouped with the other cultivars.…”
Section: Discussionsupporting
confidence: 91%
“…In our previous study, the 21 cultivars constituted a core collection of Chinese cultivated strains9, while 35 out of the 39 wild strains constituted a core collection of Chinese wild strains. Core collection is a subset of accessions representing the maximum possible genetic diversity contained in the entire collection with minimum repetition16.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixty L. edodes strains from wild and cultivation strains [32,33] were used to screen thermotolerance in this study by primarily observing the mycelial recovery. The well-grown mycelial plugs were inoculated into sawdust plates (78 g of hardwood sawdust, 20 g of wheat bran, 2 g of lime and 20 g of agar in 1 L of distilled water).…”
Section: Mushroom Strains Growth Conditions and Thermotolerance Assaymentioning
confidence: 99%
“…Analysis of the genetic relationship between the relevant strains and the association of DNA markers in mushrooms can effectively increase breeding efficiency [9], because molecular markers save time in the selection process of the strain. During the last few decades, studies on the genetic diversity and population genetics in shiitake mushrooms have been conducted using various types of molecular markers, including restriction fragment length polymorphism (RFLP) [10], random amplified polymorphic DNA (RAPD) [11,12,13], amplified fragment length polymorphism (AFLP) [14], inter-simple sequence repeat (ISSR) [12,15,16], sequence-characterized amplified region (SCAR) [13,17,18], and sequence-related amplified polymorphism (SRAP) [12,16]. In spite of their diverse applications, the use of developed markers for the breeding and classification of shiitake mushrooms has been challengeable due to few available markers and little information regarding effectiveness for determination and specificity.…”
Section: Introductionmentioning
confidence: 99%